2018
DOI: 10.1002/joc.5891
|View full text |Cite
|
Sign up to set email alerts
|

Effects of two different La Niña types on the South American rainfall

Abstract: The paper tests if the two La Niña (LN) types can be distinguished from each other using their climate impacts on northeastern Brazil (NEB). To this end, all LN events during the 1901–2010 period followed by a wet or dry rainy season (from February to April) in NEB are classified into two categories: WET‐LN and DRY‐LN. The global and regional anomalous atmospheric circulation patterns and the rainfall anomaly patterns in South America associated with the two cases are analysed. The WET‐LN and DRY‐LN events pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 36 publications
(85 reference statements)
1
8
0
Order By: Relevance
“…Using the times series of southern Amazon CO for July-October 2000-18, it is evident from the field correlation maps (Figs. 4d-f) that cooler sea temperatures and higher pressure in the east Pacific Ocean enhance fire emissions, consistent with La Niña (Andreoli et al 2018). 500-hPa zonal wind correlations indicate westerlies (1r) over Peru and easterlies (2r) over Brazil: opposing flows that confine the smoke plumes.…”
Section: Interannual Variabilitysupporting
confidence: 56%
“…Using the times series of southern Amazon CO for July-October 2000-18, it is evident from the field correlation maps (Figs. 4d-f) that cooler sea temperatures and higher pressure in the east Pacific Ocean enhance fire emissions, consistent with La Niña (Andreoli et al 2018). 500-hPa zonal wind correlations indicate westerlies (1r) over Peru and easterlies (2r) over Brazil: opposing flows that confine the smoke plumes.…”
Section: Interannual Variabilitysupporting
confidence: 56%
“…According to Andreoli et al . (2019) the years 1989 and 2008 were classified as wet La Niña years, when La Niña events are followed by anomalous wetness during the rainy season. The authors also reported that during wet La Niña events the negative SST anomalies in the eastern Tropical Pacific propagate westward during the development and maturing of the phenomenon.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, the descending anomalous motions occur in the 165°E–130°W and 20°–0°W bands, and around 80°W, and the ascending ones in the 120°–160°E and 70°–50°W bands (Figure f). It should be noted that a double Walker anomalous cell is a characteristic of the events CPLN (Xu et al ., ; Andreoli et al ., ). During D(0)JF(+1) in the CAMO, the anomalous Walker circulation weakens in relation to that of the WAMO and the double Walker cell is established (Figure e,g).…”
Section: Resultsmentioning
confidence: 99%